2016
DOI: 10.1161/strokeaha.115.011230
|View full text |Cite
|
Sign up to set email alerts
|

Combining Growth Factor and Bone Marrow Cell Therapy Induces Bleeding and Alters Immune Response After Stroke in Mice

Abstract: Background and Purpose-Bone marrow cell (BMC)-based therapies, either the transplantation of exogenous cells or stimulation of endogenous cells by growth factors like the granulocyte colony-stimulating factor (G-CSF), are considered a promising means of treating stroke. In contrast to large preclinical evidence, however, a recent clinical stroke trial on G-CSF was neutral. We, therefore, aimed to investigate possible synergistic effects of co-administration of G-CSF and BMCs after experimental stroke in mice t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…However, not all trials were successful. A recent study revealed potential side effects that are harmful in ischemic stroke when hBMSC were transplanted with granulocyte colony-stimulating factor, leading to findings of increased hemorrhagic transformation and astrogliosis with alterations in the blood-brain barrier (46). In the present study, the results seem to show an additive or synergistic effect of combined treatment with hUCBC and EPO, without a diluting effect, both for neurogenesis and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all trials were successful. A recent study revealed potential side effects that are harmful in ischemic stroke when hBMSC were transplanted with granulocyte colony-stimulating factor, leading to findings of increased hemorrhagic transformation and astrogliosis with alterations in the blood-brain barrier (46). In the present study, the results seem to show an additive or synergistic effect of combined treatment with hUCBC and EPO, without a diluting effect, both for neurogenesis and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…By modulating the inflammatory processes, transplanted cells increase their own chances of survival. Otherwise, such processes can result in failure to survive or engraft, bleeding, altered immune responses and can reduce or even eliminate the therapeutic effects of transplantation (Strecker et al, 2016). …”
Section: Limitations and Potential Adverse Effectsmentioning
confidence: 99%
“…Seventy-two adult male C57BL/6 mice received either high-salt diet containing 4% NaCl (ssniff, Germany) and tap water containing 1% NaCl ad libitum (high-salt, n = 36) or standard diet and tap water ad libitum (standard, n = 36), as previously described [3,4]. Seven days after the initiation of high-salt diet, ischemic stroke was induced by transient middle cerebral artery occlusion (MCAO) as previously described [15,16]. To evaluate whether high-salt diet had an impact on functional outcomes, neurological deficit score assessment was performed according to a modification of Menzies neuroscore [15], which showed significantly worse outcomes following high-salt diet (p<0.05, 2way ANOVA, Fig 1A).…”
Section: Resultsmentioning
confidence: 99%
“…The total number of F4/80 + -microglia/macrophages was significantly reduced after high-salt diet (p<0.01, t-test, Fig 2B). In particular, the number of cells expressing Arginase-1, an exemplary marker for anti-inflammatory microglia/macrophages [16,19], was reduced following high-salt diet (p<0.05, t-test, Fig 2C). CD16/32 + -cells, indicating pro-inflammatory microglia/macrophages [19,20], were unaltered (p = 0.28, t-test, Fig 2C).…”
Section: Resultsmentioning
confidence: 99%